The Health Promotion Innovation of Thai Muslim Older Persons by an Exercise Program with Pencak Silat Movements - Adulyarat, Manassavee; Adulyarat, Najmee; Dahamang, Suraida; Awae, Nur-Amanee; Alee, Yusrau (Princess of Naradhiwas University Journal, 2021)
This study aimed to develop an innovation to improve well-being among the older Thai Muslims using an exercise program with Pancak Silat movements. The research included 2 steps: 1) analyzing the context of the area and assessing the needs of the exercise of the older Thai Muslims. Data were collected by focus group discussion from 8 informants, selected by purposive sampling and analyzed with content analysis and 2) developing innovations to improve well-being among the older Thai Muslims through exercise programs with the Pancak Silat movements. A purposive sample of 31 older persons was selected to assess the innovation of exercise programs through the opinion assessment form. Data were analyzed by distribution of frequency, percentage, mean and standard deviation. Acquiring Pencak Silat, the established invention resulted in 10 suitable postures with 40 minutes of exercise, using a cappella rhythm to harmonize with Thai Muslim doctrine. The exercise manual and VDO clip included two languages: Thai and a local Malay dialect. The questionnaire revealed that overall opinions in term of exercise program, and opinions in term of attitude were high ( ), ( ), and ( ), respectively. Item analysis demonstrated that Language in media received highest score in group of exercise program ( ). For attitudes, the highest score item was agreeable to folk culture ( ). This study discovered that an exercise program based on Pencak Silat is an innovative and practical exercise program that meets the needs of older Thai Muslims in three southern border provinces.